Commentary on the Article “Multiple Hormonal and Metabolic Deficiency Syndrome Predicts Outcome in Heart Failure: The T.O.S.CA. Registry”, Antonio Cittadini et al. Eur. J. Prev. Cardiol. 2021 - Triggiani, Vincenzo; Lisco, Giuseppe (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Chronic heart failure represents a relevant concern for public health. The endocrine system is heavily involved in the induction and progression of chronic heart failure. Among endocrine disorders, the most relevant alterations are related to the growth hormone-insulin like growth factor 1 axis, serum testosterone, dehydroepiandrosterone sulfate, triiodothyronine levels, insulin resistance, and type 2 diabetes mellitus. It is currently debated whether these changes might be simple adaptive mechanisms or, instead, they may deteriorate myocardial pump function over time. In this commentary on a recently published paper by Antonio Cittadini et al. (Eur J Prev Cardiol. 2021), we briefly presented and discussed data form the “Trattamento Ormonale nello Scompenso CArdiaco; Hormone Treatment in Heart Failure (TOSCA) Registry”. One or more hormonal deficiencies or metabolic disorders, including insulin resistance and diabetes mellitus, were more commonly diagnosed in patients with heart failure (358 patients, 75% of study group). The presence of multiple hormone deficiency identified a subset of patients at increased risk of hospitalization and death, with a graded relation between the number of deficiencies and total events. This finding suggests a possible causal role of hormone deficiencies in CHF progression. Screening of hormonal and metabolic imbalances in CHF patients would be an interesting opportunity for improving the prognosis of patients with heart failure as it would identify high-risk patients requiring an additional medical management of the underlying endocrine and metabolic disorders.
Keywords: dehydroepiandrosterone sulfate